Atensi masyarakat dalam menggunakan peer to peer lending syariah: Mendorong inklusi keuangan syariah - Aisah, Nurul; Rizkiawan, Ilham Karin; Sholeha, Antik (Nur Science Institute, 2024)
Compared with conventional online loans, there are probably few people interested in sharia loans. Nevertheless, Indonesia is the country with the largest Muslim population in the world. This research aims to find components influencing people's use of the Sharia P2P Lending platform. A quantitative approach was taken in the research, and data was collected through an empirical survey using a purposive sampling method. The inclusion criteria for respondents were Muslims who knew or had used Sharia P2P Lending. The number of samples obtained was 100 respondents. In addition, the analysis was carried out with Smart PLS using Structural Equation Modeling (SEM). The research results show that the trust variable significantly influences attitudes and interests. The risk perception variable has a significant negative effect on attitudes and interests. The attitude variable significantly affects interest and can mediate the relationship between trust risk perception and interest in using Sharia Peer Lending.